Aging of ceramic coated graphitic negative and NCA positive electrodes in commercial lithium-ion battery cells – An ex-situ study of different states of health for identification and quantification of aging influencing parameters. (October 2017) - Börger, Elisabeth M.; Jochler, Enrica; Kaufmann, Jörg; Ramme, Rolf; Grimm, Andreas; Nowak, Sascha; Schappacher, Falko M.; Rodehorst, Uta; Voigt, Arne-Christian; Passerini, Stefano; Winter, Martin; Börger, Alexander
Highlights: Lithium loss of the cathode is correlated with lithium increase of the anode. The linearity of the lithium content in the electrodes is a function of SOH. The lithium content in the electrodes is an exponential function of the porosity. Another aging effect is the degradation of the ceramic coating on the graphite. A migration of the ceramic coating from the anode surface to the bulk occurs. Abstract: An ex-situ aging study was carried out using commercial lithium-ion battery cells with lithium nickel cobalt aluminum oxide (NCA) positive electrodes and aluminum oxide (Al2O3) surface coated graphitic negative electrodes at various states of health (SOHs): 100%, 80% and 10%. The lowest SOH-value was chosen in order to understand and to quantify the aging mechanisms in lithium-ion batteries. The electrodes were analyzed by different techniques: SEM/EDX, ICP-OES, XPS, XRD and BET. Significant changes in positive and negative morphology, elemental composition and surface area were observed depending on the SOH value and the positioning of the sample in the jelly roll. We discuss in the context of well-known aging mechanisms further aging effects. The cell capacity is limited by the amount of immobilized lithium. Lithium loss of the positive electrode is directly correlated with a lithium increase of the negative electrode. The linearity of the lithium content in the electrodes is a function of SOH over the whole SOH-range while the lithium content in the electrodes is an exponential function of the porosity. Another aging effect is the degradation of the ceramic coating on the graphite and the migration of the ceramic coating from the surface of the negative electrode to the bulk.